2014
DOI: 10.9790/3008-09621622
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of genetic variation and changes in protein subunits induced by petroleum oil in three species of Red Sea fishes using SDS-PAGE and ISSRs markers

Abstract: Genetic variability among three species of red sea fishes (Lethrinus borbonicus, Siganus rivulatus and Mulloidichthys flavolineatus) were determined to evaluate the effect of petroleum oil component pollutions on the fishes using Inter-simple sequence repeats (ISSRs) and sodium dodecyl sulfate-polyacrlamide gel electrophoresis (SDS-PAGE) markers. According to ISSR analysis of DNA, nineteen (19) ISSR primers generated a total of 465 bands with an average 24.5 bands per primer. Analyses of SDS-PAGE protein, 137 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…In addition, El-Khayat et al (2017) succeeded to differentiate among five snail groups; three were under the selective pressure for Cd tolerance through successive three generation; G1, G2 &G3; and two non-selected snail groups, parent field and lab B. alexandrina. Their results revealed that G3 snail group was the most unique by total 25 polymorphic bands produced by ten primers, 16 absence and 9 excess.These results were in agreement with Ebied et al(2014) who identifying that petroleum oil components pollution have distinct effect on genetic structure of fishes and with Saravanan et al, (2011) who reported that fish are used as excellent indicator of aquatic pollution due to their high sensitivity to environmental contamination which may change certain physiological and biochemical processes when contact with the organs of fishes. The efficiency of ISSR markers in this study was very satisfactory, supporting previous studies of genetic diversity evaluation in fish species, such as Cichla (Almeida-Ferreira et al, 2011), Astyanax fasciatus (Pazza et al, 2007).…”
Section: Discussionsupporting
confidence: 81%
“…In addition, El-Khayat et al (2017) succeeded to differentiate among five snail groups; three were under the selective pressure for Cd tolerance through successive three generation; G1, G2 &G3; and two non-selected snail groups, parent field and lab B. alexandrina. Their results revealed that G3 snail group was the most unique by total 25 polymorphic bands produced by ten primers, 16 absence and 9 excess.These results were in agreement with Ebied et al(2014) who identifying that petroleum oil components pollution have distinct effect on genetic structure of fishes and with Saravanan et al, (2011) who reported that fish are used as excellent indicator of aquatic pollution due to their high sensitivity to environmental contamination which may change certain physiological and biochemical processes when contact with the organs of fishes. The efficiency of ISSR markers in this study was very satisfactory, supporting previous studies of genetic diversity evaluation in fish species, such as Cichla (Almeida-Ferreira et al, 2011), Astyanax fasciatus (Pazza et al, 2007).…”
Section: Discussionsupporting
confidence: 81%
“…This information obtained by protein separation based on their molecular weight using SDS-PAGE technique (Roy and Kumar 2012). Protein profiles have been used as markers for genetic diversity assessment of the freshwater fish, including snapper fish (Lutjanidae) (Velamala et al 2017), snakehead (Channidae) (Haniffa et al 2017), Oreochromis niloticus (Elghobashy et al 2005), Carp (Saxena and Soranganba 2014), Lethrinus borbonicus, Siganus rivulatus and Mulloidichthys flavolineatus (Ebied et al 2014), and Labeo rohita and Cirrhinus mrigala (Mahboob et al 2012). Therefore, this study proposed to access genetic diversity of Anabantoidei fish collected from South Kalimantan based on protein profiles obtained from SDS-PAGE analysis.…”
Section: Introductionmentioning
confidence: 99%